Produção de biodiesel em escala piloto via hidroesterificação enzimática - Wancura, João Henrique Cabral (2021)
The report “State of the Climate” released by the World Meteorological Organization at 25th Climate Changes Conference highlights that 2019 ends an alarming decade regarding the historical increase in the average temperature of the planet and record rise in sea level. Such environmental problems were enhanced by the emission of greenhouse gases expelled mainly from the burning of fossil fuels in internal combustion engines. In this context, biodiesel (methyl or ethyl esters of long chain fatty acids) has consolidated itself in the global energy matrix as an alternative to its similar derivative from petroleum, becoming an indispensable component to be mixed with diesel for commercialization purposes. Among the distinct ways of synthesizing biodiesel, the application of lipases in liquid formulation as reaction catalyst has the potential to make the process more economical, competitive and sustainable compared to the use of immobilized enzymes. However, despite the benefits, the long reaction times required to achieve satisfactory yields as well as the denaturing effect of methanol (the main reaction reagent) on the enzyme are still drawbacks of the process. Before the exposed, this thesis aimed to evaluate the process of obtaining biodiesel via enzymatic hydroesterification mediated by two soluble enzymes: Eversa® Transform and the recently launched thermostable lipase Eversa® Transform 2.0 (also named as NS 40116), both obtained from the Thermomyces lanuginosus microorganism and supplied by Novozymes A/K. For this, different feedstocks were employed: degummed soybean oil (the main raw material used industrially for biodiesel production), beef tallow and waste cooking oil with high acidity. Preliminary tests using the lipase Eversa® Transform demonstrated that different feeding strategies of inputs (enzyme and alcohol) to the reaction significantly impact on the reaction yield. At 35 °C, a methanol to substrate (tallow) molar ratio of 4.5:1, with alcohol feeding at constant flow of 3.0 g∙h-1, 1.0 wt% of lipase, 6.0 wt % of water and 8 h of reaction, 85.08% of FAME yield was obtained, an interesting value but below that required by regulatory standards. Thus, improvements in the process were necessary. For this, a proposal of reaction configuration in two stages showed to be effective in elevating the process productivity: using 0.70 wt% of lipase NS 40116, 35 °C, a total methanol to substrate molar ratio of 6.3:1 and 8 wt% of water, 97.1% FAME yield was achieved in 8 h of reaction. Such yield is similar to that obtained by similar researches that required up to 24 h of reaction in a single reaction stage, demonstrating that the proposed configuration is an attractive option for the process. Then, with the reaction parameters for the process in two stages optimized via experimental design, was started to assess the biotechnological route on a superior scale than the lab. Using a pilot unit with 60 L of production capacity, waste oil used as raw material and with the reaction conditions found previously in the laboratory, 96.2 % of FAME yield was achieved. Still with these results, a pseudo-first order model was proposed to adjust the experimental data, where an apparent reaction rate (kApp) of 0.373·h-1 was obtained. Moreover, an economic analysis indicated the feasibility of the system through a positive net return and an operating cost of US$ 0.50∙kg-1 of biofuel. This information served to conclude that enzymatic hydroesterification catalyzed by liquid lipases has the necessary tools to be implemented in the industrial production of biodiesel.